(untitled) (Research, Society and Development, 2021)
The paper intends to delimit the lines that circumscribe the requirements interest and legitimacy, while institutes of a new procedural legal system, that originated the 2015 Code of Civil Procedure, which expressly contemplated them as requirements to apply for a legal action. From the analysis of the theoretical construction that instituted these elements as a procedural category, it is recorded that, in essence, they are indissociable from the basic procedural structure of action, and constitute the bond through which the correspondence of the situation affirmed in judgment to that of life. It’s emphasized that the adoption of these requirements as conditions of action by the legislator of the 1973 Code of Civil Procedure derives from the great influence that Liebman exerted on Brazilian proceduralists in the last century. In moving forward, it is based on a teleological right of action model, of a complex nature, which, through an instrumentalized process, ensures to the claimants the access to a proper judicial protection to the guarantee of substantial rights. In developing, it sets out the theoretical formulations that have developed among the patrician jurists around the new clothing assigned by the legislator to the requirements interest and legitimacy. From the comparison of these constructions, it is verified that the dissonance among jurists perpasses by the nature of the exercise of cognition exercised by the magistrate in examining the requirements, but this in itself is a reflection of the true unicity between the theorists, the grouping of the procedural institutes, with the aim of establishing the process as an authentic way to provide adequate judicial protection.